THE MERITORIOUS LEARNING REWARDS PROMOTED BY CHATGPT IN ACADEMIC WRITING CLASSROOM CONTEXTS - Wijaya, Kristian (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
Most EFL learners often feel encumbered while doing academic writing tasks as they struggle with grammar, the ideation process, and proper language expression use. To better lessen this debilitating hurdle, second language educators are highly recommended to start activating the proper usage of artificial intelligence platforms in their regular academic writing learning enterprises. With this self-initiated action, language learners can potentially possess more robust readiness while confronting challenging academic writing tasks. This small-scale library investigation was initiated by the researcher to profoundly explore the potential meritorious learning rewards promoted by ChatGPT in modern academic writing classroom contexts. To achieve this major study objective, the researcher made use of a thematic analysis approach in analyzing the identical research results yielded by 20 previously published ChatGPT scientific journals. The main purpose of embedding this research methodology is to ascertain the relevancy, applicability, and robustness of independent research outcomes. Two major reasons underlie worldwide second language educationalists to internalize the ChatGPT tool at the onset of variegated academic writing classroom settings, namely the significant reduction of writing errors and the realization of proficient academic writers.